2002
DOI: 10.1021/ja0123453
|View full text |Cite
|
Sign up to set email alerts
|

Bond Insertion, Complexation, and Penetration Pathways of Vapor-Deposited Aluminum Atoms with HO- and CH3O-Terminated Organic Monolayers

Abstract: The interaction of vapor-deposited Al atoms with self-assembled monolayers (SAMs) of HS-(CH(2))(16)-X (X = -OH and -OCH(3)) chemisorbed at polycrystalline Au[111] surfaces was studied using time-of-flight secondary-ion mass spectrometry, X-ray photoelectron spectroscopy, and infrared reflectance spectroscopy. Whereas quantum chemical theory calculations show that Al insertion into the C-C, C-H, C-O, and O-H bonds is favorable energetically, it is observed that deposited Al inserts only with the OH SAM to form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
327
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(350 citation statements)
references
References 41 publications
21
327
2
Order By: Relevance
“…39,40,44 iii) Most studies have generated top-electrodes by depositing gold or titanium (using electron-beam evaporation or sputtering) onto monolayers of reactive organic molecules. 16,44 It is unlikely that the molecules are not destroyed, or that the monolayer is not penetrated by the highly energetic incoming metal atoms or clusters of atoms. 16 iv) Asymmetric placement of the donor-acceptor moiety inside the junctions may cause rectification that is not inherent to the donor-acceptor design.…”
Section: Theory Of Molecular Rectification: Requirements Of the Molecmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40,44 iii) Most studies have generated top-electrodes by depositing gold or titanium (using electron-beam evaporation or sputtering) onto monolayers of reactive organic molecules. 16,44 It is unlikely that the molecules are not destroyed, or that the monolayer is not penetrated by the highly energetic incoming metal atoms or clusters of atoms. 16 iv) Asymmetric placement of the donor-acceptor moiety inside the junctions may cause rectification that is not inherent to the donor-acceptor design.…”
Section: Theory Of Molecular Rectification: Requirements Of the Molecmentioning
confidence: 99%
“…16,44 It is unlikely that the molecules are not destroyed, or that the monolayer is not penetrated by the highly energetic incoming metal atoms or clusters of atoms. 16 iv) Asymmetric placement of the donor-acceptor moiety inside the junctions may cause rectification that is not inherent to the donor-acceptor design. Many studies involve monolayers formed by the Langmuir-Blodgett technique that requires amphiphilic molecules, in which one side of the polar D-σ-A moiety is functionalized with long alkyl tails.…”
Section: Theory Of Molecular Rectification: Requirements Of the Molecmentioning
confidence: 99%
“…In the case of self-assembled monolayers, it was observed that Al atoms exhibit a wide range of chemical and physical interactions. 26,27 For example, reactive surfaces, such as -COOH and -OH, can interact with the aluminum to form a series of organometallic complexes in the first few monolayers. In contrast, when the terminal group of the alkyl chain of the self-assembled monolayer contains an unreactive group, such as -CH 3 , penetration of the metal atoms through the monolayer occurs to the Au/ S interface where it forms an adsorbed layer.…”
Section: -8mentioning
confidence: 99%
“…Several studies [58][59][60][61][62][63] have analyzed (by X-ray photoelectron spectroscopy, infra-red spectroscopy,…) the interaction (bond insertion, complexation…) between the metal atoms and the molecules. When the metal atoms are strongly reactive with the end-groups of the molecules (e.g.…”
Section: B At the "Device-like" Levelmentioning
confidence: 99%
“…Al with COOH or OH groups, Ti with COOCH 3 , OH or CN groups….) [58][59][60][61][62][63], a chemical reaction occurs forming a molecular overlayer on top of the monolayer. This overlayer made of organometallic complexes or metal oxides may perturb the electronic coupling between the metal and the molecule, leading, for instance, to partial or total Fermi-level pinning at the interface [64].…”
Section: B At the "Device-like" Levelmentioning
confidence: 99%